Strategy for improving the quality of education through meeting the standards manpower of education in junior high school - Tina Rosalina; Happy Fitria; Achmad Wahidy (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
How much influence is the strategy for improving the quality of education through meeting education standards and education personnel. The purpose of this study is to find and describe efforts to improve education standards and education personnel in schools in terms of: planning, implementing and supervising education, influencing, directing teachers and school staff in improving the quality of education. As stated in the National Education Standards (SNP) article 1 No. 17 of Law 20/2003 on National Education System and article 3 of Government Regulation No. 19 Year 20015 that: "Where SNP functions as the basis for planning, implementation and supervision of education at the level of education to realize a national education that is of good quality and aiming at guaranteeing the quality of national education in the framework of educating the life of the State and forming a dignified national civilization ". In expressing these things the writer uses a qualitative research approach. To extract data and information from informants, the authors used participant observation, in-depth interviews, and documents in the research data collection process. The research results revealed that; in meeting education standards and education personnel can influence teachers and school management staff so that what is done is aimed at school success and achievement, in order to improve the quality of education at SMP Negeri 1 Rambang Muara Enim Regency.